Pneumocystis jiroveci Pneumonia: A Review of Management in Human Immunodeficiency Virus (HIV) and Non-HIV Immunocompromised Patients - Ibrahim, Atif; Chattaraj, Asmi; Iqbal, Qamar; Anjum, Ali; Rehman, Mohammad Ebad Ur; Aijaz, Zobia; Nasir, Fazila; Ansar, Sadia; Zangeneh, Tirdad T.; Iftikhar, Ahmad (Avicenna Journal of Medicine, 2023)
Pneumocystis jirovecii pneumonia is an opportunistic fungal infection that was mainly associated with pneumonia in patients with advanced human immunodeficiency virus (HIV) disease. There has been a decline in Pneumocystis jirovecii pneumonia incidence in HIV since the introduction of antiretroviral medications. However, its incidence is increasing in non-HIV immunocompromised patients including those with solid organ transplantation, hematopoietic stem cell transplantation, solid organ tumors, autoimmune deficiencies, and primary immunodeficiency disorders. We aim to review and summarize the etiology, epidemiology, clinical presentation, diagnosis, and management of Pneumocystis jirovecii pneumonia in HIV, and non-HIV patients. HIV patients usually have mild-to-severe symptoms, while non-HIV patients present with a rapidly progressing disease. Induced sputum or bronchoalveolar lavage fluid can be used to make a definitive diagnosis of Pneumocystis jirovecii pneumonia. Trimethoprim-sulfamethoxazole is considered to be the first-line drug for treatment and has proven to be highly effective for Pneumocystis jirovecii pneumonia prophylaxis in both HIV and non-HIV patients. Pentamidine, atovaquone, clindamycin, and primaquine are used as second-line agents. While several diagnostic tests, treatments, and prophylactic regimes are available at our disposal, there is need for more research to prevent and manage this disease more effectively.
Keywords: pneumocystis jirovecii pneumonia; pneumocystis carinii pneumonia; PJP in HIV; PJP treatment; PJP prophylaxis; steroids in PJP